ST8SIA1 Regulates Tumor Growth and Metastasis in TNBC by Activating the FAK–AKT–mTOR Signaling Pathway - Nguyen, Khoa; Yan, Yuanqing; Yuan, Bin; Dasgupta, Abhishek; Sun, Jeffrey; Mu, Hong; Do, Kim-Anh; Ueno, Naoto T.; Andreeff, Michael; Battula, V. Lokesh (Molecular cancer therapeutics, 2018)
Breast cancer stem-like cells (BCSC) are implicated in cancer recurrence and metastasis of triple-negative breast cancer (TNBC). We have recently discovered that ganglioside GD2 expression defines BCSCs and that ST8SIA1 regulates GD2 expression and BCSC function. In this report, we show that ST8SIA1 is highly expressed in primary TNBC; its expression is positively correlated with the expression of several BCSC-associated genes such as BCL11A, FOXC1, CXCR4, PDGFRβ, SOX2, and mutations in p53. CRISPR knockout of ST8SIA1 completely inhibited BCSC functions, including in vitro tumorigenesis and mammosphere formation. Mechanistic studies discovered activation of the FAK–AKT–mTOR signaling pathway in GD2+ BCSCs, and its tight regulation by ST8SIA1. Finally, knockout of ST8SIA1 completely blocked in vivo tumor growth and metastasis by TNBC cells. In summary, these data demonstrate the mechanism by which ST8SIA1 regulates tumor growth and metastasis in TNBC and identifies it as a novel therapeutic target.